Anti-corrosion adhesive tape, structure, and anti-corrosion method

By optimizing the tensile load difference value of the substrate and the composition of the adhesive layer in the anti-corrosion adhesive tape, the mechanical problems of the adhesive tape during complex surfaces and large-area construction are solved, and higher adhesion and corrosion resistance are achieved.

CN119855879APending Publication Date: 2025-04-18SEKISUI CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380065216.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-13
Filing Date
2023-09-12
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing anti-corrosion adhesive tapes are prone to wrinkles, floats and cracks during complex surface shapes and large-area construction, and the operation efficiency is low.

Method used

The difference between the tensile load at elongation of 2.5% and the tensile load at elongation of 0.5% is 1.5 N/mm or more and 6.0 N/mm or less, and the adhesive layer contains metals with lower potential than iron, such as zinc and conductive materials such as carbon nanotubes.

Benefits of technology

It improves the adhesion of the adhesive tape to complex surface shapes, inhibits wrinkles, floats and cracks during large-area construction, and improves operating efficiency and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855879A_ABST
    Figure CN119855879A_ABST
Patent Text Reader

Abstract

The present invention is an anti-corrosion pressure-sensitive adhesive tape having a base material and a pressure-sensitive adhesive layer provided on at least one surface of the base material, the difference between the tensile load at 2.5% elongation of the base material and the tensile load at 0.5% elongation of the base material being 1.5 N / mm or more and 6.0 N / mm or less, the tear strength of the base material, as measured without cutting a notch in the Elmendoff tear method in accordance with JIS K7128-2 (1998), is 1.7 N or more. A structure according to the present invention comprises the corrosion-resistant adhesive tape according to the present invention and an adherend made of a metal material or an adherend made of concrete. The corrosion-resistant adhesive tape according to the present invention is attached to the surface of the adherend. The anti-corrosion method according to the present invention comprises a first step of preparing the anti-corrosion adhesive tape according to the present invention, and a second step of attaching the anti-corrosion adhesive tape to an adherend and then peeling off the surface protective film from the anti-corrosion adhesive tape. According to the present invention, it is possible to provide: an adhesive tape for corrosion prevention, which has excellent adhesion to an adherend having a complicated surface shape, has excellent adhesion properties, and can be used for corrosion prevention, a structure having the adhesive tape for corrosion prevention, and a corrosion prevention method using the adhesive tape for corrosion prevention; and the generation of wrinkles, floating and cracks during large-area construction can be inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anti-corrosion adhesive tape, a structure having the anti-corrosion adhesive tape, and an anti-corrosion method using the anti-corrosion adhesive tape. Background Art

[0002] In order to prevent corrosion of iron or alloys containing iron such as steel, anti-corrosion coatings containing a large amount of zinc are widely used. It is known that zinc is a metal with a lower potential than iron, has a sacrificial anti-corrosion effect, and therefore has high corrosion resistance. In addition, in concrete structures, in order to prevent corrosion caused by salt damage, neutralization caused by exhaust gas, alkali-aggregate reaction, freezing of water immersed in cracks, etc., which deteriorate concrete and corrode internal steel bars, anti-corrosion coatings are also widely used. However, the anti-corrosion using coatings requires a drying process after coating, etc., which takes time in operation. For example, when local repairs are performed in civil engineering and construction applications such as bridges, the operating efficiency is reduced. In addition, the anti-corrosion using coatings is also prone to uneven operation.

[0003] In view of the above situation, research is being conducted on measures related to anti-corrosion adhesive tapes that improve workability by imparting sacrificial corrosion resistance to the tape. For example, in Patent Document 1, zinc particles and conductive fillers are included in the adhesive layer to form an electronic circuit between the zinc plate of the substrate and oxygen / water, thereby exhibiting sacrificial corrosion resistance.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-127606 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, the anti-corrosion member of patent document 1 sometimes cannot fully fit with adherends with complex surface shapes such as convexo-concave portions, and cannot fully exert the anti-corrosion property of the anti-corrosion member. In addition, the anti-corrosion member of patent document 1 sometimes produces wrinkles, or floats, or cracks when applied over a large area.

[0009] Therefore, the object of the present invention is to provide an anti-corrosion adhesive tape, a structure having the anti-corrosion adhesive tape, and an anti-corrosion method using the anti-corrosion adhesive tape, wherein the anti-corrosion adhesive tape has excellent adhesion to an adherend with a complex surface shape and can suppress the occurrence of wrinkles, lifting and cracks during large-area construction.

[0010] Means for solving problems

[0011] As a result of intensive studies, the inventors of the present application have found that the above-mentioned problems can be solved by using a substrate having a difference between a tensile load at 2.5% elongation and a tensile load at 0.5% elongation of a predetermined value or less and a tear strength of a predetermined value or more, thereby completing the present invention.

[0012] The present invention provides the following [1] to

[19] .

[0013] [1] An anti-corrosion adhesive tape comprising a substrate and an adhesive layer provided on at least one side of the substrate, wherein the difference between the tensile load of the substrate when elongated by 2.5% and the tensile load when elongated by 0.5% is 1.5 N / mm or more and 6.0 N / mm or less, and the tear strength of the substrate measured by the Elmendorf tear method based on JIS K7128-2 (1998) without cutting is 1.7 N or more.

[0014] [2] The anticorrosion adhesive tape according to [1] above, which does not generate rust in a cyclic corrosion test based on cycle D in JIS K5600-7-9 and has an adhesive strength of 20 N / 25 mm or more after the cyclic corrosion test.

[0015] [3] The anticorrosion adhesive tape according to [1] or [2], wherein the gloss retention of the substrate is 80% or more after being subjected to an accelerated weathering test based on Cycle A in JIS K5600-7-7 for 500 hours.

[0016] [4] The anticorrosion adhesive tape according to any one of [1] to [3] above, wherein the thickness of the substrate is 20 to 150 μm.

[0017] [5] The anticorrosion adhesive tape according to any one of [1] to [4] above, wherein the substrate is a resin film having a coating film on its surface.

[0018] [6] The anticorrosion adhesive tape according to [5] above, wherein the resin film is at least one resin film selected from the group consisting of polyethylene terephthalate (PET) film, stretched polypropylene (OPP) film, acrylic resin film, and polyamide resin film.

[0019] [7] The anticorrosion adhesive tape according to any one of [1] to [6] above, wherein the adhesive layer contains a metal having a lower potential than iron.

[0020] [8] The anticorrosion adhesive tape according to [7] above, wherein the metal having a lower electric potential than iron is zinc.

[0021] [9] The anticorrosion adhesive tape according to [7] or [8] above, wherein the adhesive layer contains a conductive material other than the metal having a lower potential than iron.

[0022]

[10] The anticorrosion adhesive tape according to [9] above, wherein the conductive material is carbon nanotubes.

[0023]

[11] The anticorrosion adhesive tape according to any one of [1] to

[10] above, wherein the adhesive layer is formed of an acrylic adhesive.

[0024]

[12] The anticorrosion adhesive tape according to any one of [1] to

[11] , further comprising a metal layer between the substrate and the adhesive layer, wherein the metal layer has a lower potential than iron.

[0025]

[13] The anticorrosion adhesive tape according to

[12] above, wherein the metal layer is a zinc layer.

[0026]

[14] The anticorrosion adhesive tape according to any one of [1] to

[13] above, wherein the thickness of the adhesive layer is 50 to 3000 μm.

[0027]

[15] The anticorrosion adhesive tape according to any one of [1] to

[14] above, wherein the storage elastic modulus of the adhesive layer at 23° C. is 50,000 to 1,000,000 Pa.

[0028]

[16] According to any one of [1] to

[15] above, the adhesive layer is arranged on one side of the substrate, and the anti-corrosion adhesive tape also has a surface protection film arranged on the surface of the substrate opposite to the surface of the adhesive layer and used to protect the surface of the substrate opposite to the surface of the adhesive layer.

[0029]

[17] A structure comprising the anti-corrosion adhesive tape according to any one of [1] to

[16] above and an adherend made of a metal material or an adherend made of concrete, wherein the anti-corrosion adhesive tape is attached to a surface of the adherend.

[0030]

[18] The structure according to

[17] above, wherein the anticorrosion adhesive tape has an attachment area of ​​2000 cm 2 above.

[0031]

[19] A corrosion protection method comprising the following steps: a first step of preparing the corrosion protection adhesive tape described in

[16] above, and a second step of attaching the corrosion protection adhesive tape to an adherend and then peeling off the surface protection film from the corrosion protection adhesive tape.

[0032] Effects of the Invention

[0033] According to the present invention, there can be provided an anti-corrosion adhesive tape, a structure having the anti-corrosion adhesive tape, and an anti-corrosion method using the anti-corrosion adhesive tape, wherein the anti-corrosion adhesive tape has excellent adhesion to an adherend having a complex surface shape and can suppress the occurrence of wrinkles, lifting and cracks during large-area construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] [ Figure 1 ] is a schematic diagram showing an example of use of a modified example of an anti-corrosion adhesive tape according to an embodiment of the present invention.

[0035] [ Figure 2 ] is a schematic cross-sectional view showing another embodiment of the anti-corrosion adhesive tape of the present invention.

[0036] [ Figure 3 ] is a schematic diagram showing a method for evaluating the convex followability of the anti-corrosion adhesive tape of the present invention.

[0037] [ Figure 4 ] is a diagram used to illustrate the evaluation of large-area construction performance. DETAILED DESCRIPTION

[0038] [Anti-corrosion adhesive tape]

[0039] The present invention is an anti-corrosion adhesive tape, comprising a substrate and an adhesive layer provided on at least one side of the substrate, wherein the difference between the tensile load when the substrate is elongated by 2.5% and the tensile load when the substrate is elongated by 0.5% is 1.5 N / mm or more and 6.0 N / mm or less, and the tear strength measured by the Elmendorf tear method according to JIS K7128-2 (1998) without cutting is 1.7 N or more.

[0040] <Base Material>

[0041] (Difference in tensile load)

[0042] The difference between the tensile load at 2.5% elongation and the tensile load at 0.5% elongation of the base material of the anticorrosion adhesive tape of the present invention (hereinafter, sometimes simply expressed as "tensile load difference") is 1.5 N / mm or more and 6.0 N / mm or less. The tensile load difference substantially refers to the tensile load per 2% elongation in the elastic region.

[0043] When the difference in tensile load is less than 1.5 N / mm, wrinkles may sometimes be generated in the anticorrosion adhesive tape during large-area construction. From this viewpoint, the difference in tensile load is preferably 2.0 N / mm or more, more preferably 2.5 N / mm or more, and further preferably 3.0 N / mm or more.

[0044] In addition, when the difference in tensile load is greater than 6.0 N / mm, sometimes when the anticorrosion adhesive tape is attached to an adherend having a complex surface shape, floating occurs, or floating and cracks occur during large-area construction. From such a viewpoint, the difference in tensile load is preferably 5.5 N / mm or less, more preferably 5.0 N / mm or less, and further preferably 4.5 N / mm or less.

[0045] It should be noted that the difference in tensile load is measured in the MD direction and TD direction of the substrate, and the larger one is used. In addition, when the MD direction and TD direction are unknown, the value with the largest difference in tensile load can be used. The difference in tensile load can be obtained by the measuring method described in the embodiment.

[0046] In addition, the difference in tensile load of the substrate can be adjusted within the above range by appropriately selecting the material used for the substrate, the thickness of the substrate, etc. Specifically, the material used for the substrate is preferably a resin film, particularly preferably a PET (polyethylene terephthalate) film or an OPP (stretched polypropylene) film. The thickness of the substrate is preferably in the range described below.

[0047] (Tear Strength)

[0048] In the base material used for the anticorrosion adhesive tape of the present invention, the tear strength measured in the Elmendorf tearing method based on JIS K7128-2 (1998) without cutting the incision is 1.7N or more. When the tear strength of the base material measured without cutting the incision is less than 1.7N, when the anticorrosion adhesive tape is intended to be adhered to an adherend with a complex surface shape, floating and cracks are sometimes generated in the anticorrosion adhesive tape. In addition, when a large area is constructed, floating and cracks are sometimes generated in the anticorrosion adhesive tape. From such a viewpoint, the tear strength of the base material measured without cutting the incision is preferably 3.0N or more, more preferably 6.0N or more, and further preferably 12N or more.

[0049] The higher the tear strength of the substrate measured without cutting, the better, and the upper limit of the range is, for example, 16N.

[0050] It should be noted that the tear strength of the substrate measured without cutting the incision is measured in the MD direction and TD direction of the substrate, and the smaller one is adopted. In addition, when the MD direction and the TD direction are unclear, the minimum tear strength value can be adopted. The tear strength of the substrate measured without cutting the incision can be measured by the same method as the Elmendorf tearing method based on JIS K7128-2 (1998), except that this point is measured without cutting the incision.

[0051] In addition, the tear strength of the substrate measured without cutting the incision can be adjusted to the above range by appropriately selecting the material used by the substrate, the thickness of the substrate, etc. Specifically, the material used by the substrate is preferably a resin film, particularly preferably a PET film, an OPP film, more preferably a biaxially stretched PET film, a biaxially stretched OPP film. The thickness of the substrate is preferably in the range described later.

[0052] (Material used for base material)

[0053] Examples of the substrate used in the present invention include sheet-like materials such as resin films and nonwoven fabrics.

[0054] The resin film includes, for example, polyolefin resin films such as polypropylene resin films, polyethylene resin films, and ethylene-vinyl acetate copolymer (EVA) resin films, polyester resin films, polyamide resin films (nylon), acrylic resin films, polyurethane resin films, polystyrene resin films, polyvinyl chloride resin films, ethylene vinyl acetate resin films, acrylonitrile resin films, fluorine films, polycarbonate films, AES resin films, ASA resin films, etc.

[0055] The nonwoven fabric is made of synthetic resin fibers such as polyamide, polyester, polyacrylic acid, polyolefin, and polyurethane.

[0056] These sheet materials can be used alone or in combination. From the viewpoint of the difference between the above-mentioned tensile load and the viewpoint of the above-mentioned tear strength, the substrate is preferably a resin film, more preferably a polypropylene resin film, a polyester resin film, an acrylic resin film and a polyamide resin film, and more preferably a stretched polypropylene (OPP) film, a polyethylene terephthalate (PET) film, an acrylic resin film and a polyamide resin film.

[0057] The resin film may be a single-layer film or a multilayer film in which two or more types of the above-mentioned films are laminated.

[0058] From the viewpoint of improving weather resistance, an ultraviolet absorber, a light stabilizer (HALS), or the like may be blended into the resin constituting the base material.

[0059] In addition, from the viewpoint of improving weather resistance and improving strength, the substrate can be a resin film having a coating film on the surface. The coating film is preferably a resin film, more preferably a urethane resin film, an epoxy resin film and a fluororesin film, further preferably a fluororesin film, and further preferably a difluorinated fluororesin film and a trifluorinated fluororesin film. The coating film can be arranged on one side of the substrate or on both sides, but is preferably arranged at least on the side opposite to the side of the substrate provided with the adhesive layer. By using these coating films, the weather resistance of the anticorrosive adhesive tape can be further improved, and the gloss retention rate described later can be further improved.

[0060] (Gloss retention of substrate after accelerated weathering test)

[0061] The anticorrosion adhesive tape of the present invention preferably has a gloss retention rate of 80% or more of the base material after the accelerated weathering test based on cycle A in JIS K5600-7-7 is carried out for 500 hours. By making the gloss retention rate 80% or more, even if the anticorrosion adhesive tape is exposed to light for a long time, the degradation of the base material can be prevented, and the deterioration of the appearance of the anticorrosion adhesive tape can be prevented. In addition, it is possible to fully block light such as sunlight (especially ultraviolet rays), and the degradation of the adhesive layer and the reduction of the adhesive force of the anticorrosion adhesive tape can be prevented.

[0062] From such a viewpoint, the gloss retention rate of the substrate constituting the anticorrosion adhesive tape of the present invention is preferably 85% or more, more preferably 90% or more. The higher the gloss retention rate, the better, and the upper limit is 100%.

[0063] The method for making the gloss retention rate above the above lower limit is not particularly limited, and a weather-resistant substrate can be used as the substrate. A weather-resistant resin can be used in the resin constituting the substrate so that the substrate itself has weather resistance. In addition, the weather resistance can also be improved by adding an ultraviolet absorber, a light stabilizer (HALS), etc. to the resin constituting the substrate.

[0064] In addition, for example, the above-mentioned paint film having weather resistance may also be provided.

[0065] In addition, the gloss retention rate can be measured by the following method.

[0066] An anti-corrosion adhesive tape (width 25 mm, length 100 mm) is attached, and the surface of the tape, and thus the substrate side, is measured for the specular gloss of the substrate using a gloss meter (e.g., manufactured by Horiba, Ltd., product name: "IG-340"). In the measurement of the specular gloss, the gloss meter with a geometric condition of 60° is used in accordance with JIS K 5600-4-7. The specular gloss obtained by the measurement at this time is referred to as specular gloss A. Then, for the tape, an accelerated weathering test based on cycle A in JIS K 5600-7-7 is performed for 500 hours. After the accelerated weathering test is performed, the specular gloss of the substrate of the tape is measured by the same method as that performed before the test. The specular gloss obtained by the measurement after the test is referred to as specular gloss B. Using the two specular glosses obtained as described above, the gloss retention rate of the tape is calculated. The formula for calculating the gloss retention rate is as follows. Gloss retention rate (%) = (specular gloss B / specular gloss A) × 100

[0067] (Thickness of substrate)

[0068] The thickness of the substrate is not particularly limited, but is preferably 20 to 150 μm, more preferably 40 to 140 μm, further preferably 60 to 130 μm, and further preferably 80 to 120 μm. By making the thickness of the substrate above these lower limits, it is easier to make the tear strength of the substrate measured without cutting the incision to be more than 1.7N. In addition, it is easier to make the difference in tensile load to be less than 6.0N / mm. In addition, by making the thickness of the substrate below these upper limits, it is easier to make the difference in tensile load to be more than 1.5N / mm.

[0069] <Adhesive Layer>

[0070] The anticorrosion adhesive tape of the present invention has an adhesive layer on at least one side of a substrate. The adhesive layer will be described below.

[0071] (Metal with lower electric potential than iron)

[0072] When the adhesive layer is used for attachment to steel materials, it is preferred that the adhesive layer contains a metal having a lower potential than iron. By containing a metal having a lower potential than iron (hereinafter also referred to as "sacrificial anti-corrosion metal"), the anti-corrosion adhesive tape has sacrificial anti-corrosion properties, and the anti-corrosion properties of the anti-corrosion adhesive tape are improved. The sacrificial anti-corrosion metal is dispersed in the adhesive constituting the adhesive layer.

[0073] Examples of sacrificial anticorrosion metals include cadmium, chromium, zinc, manganese, and aluminum. Among them, zinc and aluminum are preferred, and zinc is particularly preferred. The use of zinc provides excellent sacrificial anticorrosion properties.

[0074] The sacrificial anticorrosion metal can be dispersed in the adhesive as a filler in any form such as particle shape, scale shape, spindle shape, etc., but is preferably in particle shape. By making the sacrificial anticorrosion metal in particle shape, it is easy to disperse in the adhesive layer without almost reducing the adhesiveness of the adhesive layer.

[0075] In this specification, the so-called particle shape is a shape in which the ratio of the length in the long axis direction to the length in the short axis direction (aspect ratio) is small, for example, the aspect ratio is 3 or less, preferably 2 or less. The particle shape is not particularly limited, and can be spherical or amorphous such as powder. The particle size of the above-mentioned metal in particle shape is, for example, 1 to 500 μm, preferably 1 to 200 μm. It should be noted that in this specification, the so-called particle size refers to the average particle size measured by laser diffraction method.

[0076] The content of the sacrificial anticorrosion metal in the adhesive layer is, for example, 0.5 to 20 mass %, preferably 1 to 18 mass %, and more preferably 2 to 16 mass %, based on the total amount of the adhesive layer.

[0077] When the content of the sacrificial anticorrosion metal is at least these lower limits, the sacrificial anticorrosion property is improved, thereby improving the anticorrosion performance, and when the content of the sacrificial anticorrosion metal is at most these upper limits, the adhesive force is increased.

[0078] The adhesive layer may not contain a sacrificial anticorrosion metal. When the sacrificial anticorrosion metal is not contained, the adhesive force of the anticorrosion adhesive tape is maintained at a high level compared to when the sacrificial anticorrosion metal is contained, so it becomes difficult to peel off from the adherend, thereby blocking water and oxygen and easily improving corrosion resistance.

[0079] (Conductive material)

[0080] The adhesive layer preferably contains a conductive material other than the sacrificial anticorrosion metal in addition to the sacrificial anticorrosion metal. If the conductive material is contained, the electrons released when the sacrificial anticorrosion metal is ionized can be easily transferred to the adherend, and the sacrificial anticorrosion property can be easily improved.

[0081] Examples of the conductive material include one or more selected from carbon-based materials, metal-based materials, metal oxide-based materials, ionic polymers, and conductive high molecules.

[0082] As carbon-based materials, carbon black, graphite, graphene, carbon nanotubes, acetylene black, etc. can be cited. As metal-based materials, metals or iron with higher potential than iron, such as gold, silver, copper, nickel or alloys thereof, can be cited. As metal oxide materials, for example, indium tin oxide (ITO), antimony trioxide (ATO), fluorine-doped tin oxide (FTO), zinc oxide, etc. can be cited. As conductive polymers, polyacetylene, polypyrrole, PEDOT (polyethylene dioxythiophene), PEDOT / PSS (complex of polyethylene dioxythiophene and polystyrene sulfonic acid), polythiophene, polyaniline, polyparaphenylene, polyfluorene, polycarbazole, polysilane or their derivatives can be cited. As ionic polymers, sodium polyacrylate, potassium polyacrylate, etc. can be cited.

[0083] As the conductive material, these may be used alone or in combination of two or more.

[0084] Among the above, as the conductive material, a carbon-based material is preferred, and a carbon nanotube is more preferred.

[0085] (Carbon Nanotubes)

[0086] The adhesive layer preferably contains carbon nanotubes. By containing carbon nanotubes, the sacrificial corrosion resistance of the adhesive layer is improved, and the adhesive force can be maintained at a high level, so it is easy to obtain an anti-corrosion adhesive tape that achieves both high adhesive force and sacrificial corrosion resistance. It is speculated that this is because, although carbon nanotubes are conductive materials, compared with other types of conductive materials, the amount required to exhibit a certain sacrificial corrosion resistance is small, so the degree of reduction in adhesive force is small.

[0087] Carbon nanotubes are tubular materials made of carbon. Carbon nanotubes have excellent electrical properties, and when combined with resins or the like, they can form highly conductive sheets or the like. Carbon nanotubes are a material having a structure in which graphite sheets of hexagonal carbon atoms are arranged in a network and wound into a cylindrical shape. Carbon nanotubes wound in one layer are called single-walled carbon nanotubes, and carbon nanotubes wound in multiple layers are called multi-walled carbon nanotubes.

[0088] In the anticorrosion adhesive tape of one embodiment of the present invention, the type of carbon nanotube is not particularly limited, and may be any carbon nanotube in a single-walled carbon nanotube, a multi-walled carbon nanotube, or a mixture thereof in any proportion. In addition, carbon nanotubes produced by various methods such as arc discharge method, laser evaporation method, and chemical vapor deposition method (CVD method) may be used.

[0089] The average diameter of the carbon nanotubes is preferably 1 to 100 nm, more preferably 2 to 15 nm. The average length of the carbon nanotubes is preferably 0.1 to 1000 μm, more preferably 10 to 500 μm. The aspect ratio (average length / average diameter) of the carbon nanotubes is preferably 10 to 100,000, more preferably 500 to 30,000.

[0090] It should be noted that the diameter of the carbon nanotube refers to the outer diameter in the case of single-walled carbon nanotubes, and refers to the outer diameter of the outermost tube in the case of multi-walled carbon nanotubes. The diameter and length of the carbon nanotube can be measured from an image obtained by observation using a TEM (transmission electron microscope), for example, and the average diameter and average length can be obtained by arithmetic averaging of any 50 nanotubes.

[0091] From the viewpoint of the sacrificial corrosion resistance and adhesive strength of the adhesive layer, the content of the conductive material in the adhesive layer is preferably 0.005 to 10% by mass, more preferably 0.005 to 5% by mass, and even more preferably 0.006 to 3% by mass based on the total amount of the adhesive layer.

[0092] When the conductive material is carbon nanotubes, the content of the carbon nanotubes in the adhesive layer is preferably 0.0005 to 0.7 mass %, more preferably 0.005 to 0.05 mass %, and even more preferably 0.006 to 0.045 mass %, based on the total amount of the adhesive layer.

[0093] When the content of the carbon nanotubes is at least these lower limits, the sacrificial corrosion protection is easily improved, and when the content of the carbon nanotubes is at most these upper limits, the adhesive force is easily improved.

[0094] (Adhesive)

[0095] The adhesive layer is preferably formed of an adhesive. The type of adhesive is not particularly limited, and examples thereof include acrylic adhesives, rubber adhesives, urethane adhesives, and silicone adhesives. These adhesives may be used alone or in combination.

[0096] Among them, the pressure-sensitive adhesive layer is preferably formed of an acrylic pressure-sensitive adhesive.

[0097] (Acrylic adhesive)

[0098] The acrylic pressure-sensitive adhesive contains an acrylic polymer obtained by polymerizing a polymerizable monomer including an alkyl (meth)acrylate monomer (A).

[0099] It should be noted that, in this specification, the term "alkyl (meth)acrylate" refers to a concept including both alkyl acrylate and alkyl methacrylate, and the same applies to other similar terms. In addition, the term "polymerizable monomer" refers to a concept including not only compounds having no repeating units, but also compounds having repeating units in the monomer itself, such as the olefin polymer (C) described later, if copolymerized with the alkyl (meth)acrylate monomer (A).

[0100] ((Meth)acrylic acid alkyl ester monomer (A))

[0101] The (meth)acrylic acid alkyl ester monomer (A) is an ester of (meth)acrylic acid and an aliphatic alcohol, and is preferably an aliphatic alcohol alkyl ester in which the carbon number of the alkyl group derived from the aliphatic alcohol is preferably 2 to 14, more preferably 4 to 10. When the carbon number of the alkyl group is within this range, the adhesive force can be easily improved, and the storage modulus of the adhesive described later at 23° C. can be easily adjusted to a predetermined range.

[0102] Specific examples of the (meth)acrylate alkyl ester monomer (A) include ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, and tetradecyl (meth)acrylate.

[0103] Among them, n-butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and n-octyl (meth)acrylate are preferred, and n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, or a combination thereof is more preferred.

[0104] The (meth)acrylic acid alkyl ester-based monomer (A) may be used alone or in combination of two or more.

[0105] The structural unit from the (meth) alkyl ester monomer (A) is a unit constituting the main component in the adhesive layer, and its content is usually 30% by mass or more, preferably 50% by mass or more, and more preferably 70% by mass or more, based on the total amount of the adhesive layer. If the content of the (meth) alkyl ester monomer (A) is increased in this way, the desired adhesive force can be imparted to the adhesive layer. In addition, in order to contain a certain amount of other components, the above-mentioned content of the structural unit from the (meth) alkyl ester monomer (A) is, for example, 97% by mass or less, preferably 95% by mass or less, and more preferably 90% by mass or less.

[0106] It should be noted that the content of the structural unit derived from the (meth) alkyl acrylate monomer (A) in the adhesive layer is substantially the same as the content of the (meth) alkyl acrylate monomer (A) in the adhesive composition described later, and therefore can be expressed interchangeably. The same applies to the components other than the (A) component, such as the (B) and (C) components described below.

[0107] (Polar group-containing vinyl monomer (B))

[0108] The polymerizable monomer preferably includes a vinyl monomer (B) containing a polar group in addition to the (meth) alkyl acrylate monomer (A). The vinyl monomer (B) containing a polar group is a monomer having a polar group and a vinyl group. By using a monomer (B) containing a polar group, it is easy to improve the adhesive force to the adherend.

[0109] Examples of the polar group-containing vinyl monomer (B) include carboxylic acid vinyl esters such as vinyl acetate; vinyl group-containing carboxylic acids and anhydrides thereof such as (meth)acrylic acid and itaconic acid; vinyl monomers having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone-modified (meth)acrylate, polyoxyethylene (meth)acrylate, and polyoxypropylene (meth)acrylate; and nitrogen-containing vinyl monomers such as (meth)acrylonitrile, N-vinyl pyrrolidone, N-vinyl caprolactam, N-vinyl laurolactam, (meth)acryloyl morpholine, (meth)acrylamide, dimethyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, and dimethylaminomethyl (meth)acrylate.

[0110] Among them, vinyl group-containing carboxylic acids such as (meth)acrylic acid and itaconic acid and their anhydrides are preferred, (meth)acrylic acid is more preferred, and acrylic acid is further preferred. These polar group-containing vinyl monomers (B) may be used alone or in combination of two or more.

[0111] When a polar group-containing vinyl monomer (B) is used, the content of the structural unit derived from the polar group-containing vinyl monomer (B) is preferably 1 to 15 parts by mass, more preferably 2 to 12 parts by mass, and further preferably 3 to 10 parts by mass, relative to 100 parts by mass of the structural unit derived from the (meth) alkyl acrylate monomer (A) in the adhesive layer. By making the content of the polar group-containing vinyl monomer (B) within such a range, it is easy to improve the adhesive force of the anticorrosive adhesive tape.

[0112] (Olefin polymer (C))

[0113] The polymerizable monomer preferably further includes an olefin polymer (C) having a polymerizable bond at one terminal. By using such an olefin polymer (C), the adhesive strength of the anticorrosion adhesive tape can be easily improved.

[0114] The polymerizable bond refers to an unsaturated carbon-carbon bond that can be polymerized with a polymerizable monomer, and examples thereof include an unsaturated double bond, and preferably a (meth)acryloyl group or the like is used.

[0115] Examples of the olefin polymer (C) include polyolefins having a (meth)acryloyl group at one terminal. The polyolefin is a polymer of an aliphatic hydrocarbon compound having a double bond such as ethylene, propylene, butane, butadiene, isoprene, or a hydrogenated product thereof.

[0116] Examples of polyolefins having a (meth)acryloyl group at one end include polyethylene having a (meth)acryloyl group at one end prepared by reacting polyethylene having an epoxy group at one end with (meth)acrylic acid, etc. In addition, examples include polybutadiene having a (meth)acryloyl group at one end or its hydrogenated product, and examples of commercial products thereof include "L-1253" manufactured by Kuraray Co., Ltd.

[0117] The number average molecular weight of the olefin polymer (C) is preferably 500 to 20000, more preferably 1000 to 10000. The number average molecular weight can be measured by gel permeation chromatography (GPC) and calculated using a calibration curve of standard polystyrene.

[0118] In the pressure-sensitive adhesive layer, the content of the structural unit derived from the olefin polymer (C) is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and even more preferably 4 to 12 parts by mass, based on 100 parts by mass of the structural unit derived from the (meth)acrylate alkyl ester monomer (A).

[0119] (Crosslinking agent (D))

[0120] The polymerizable monomer preferably further comprises a crosslinking agent. As the crosslinking agent, a multifunctional monomer having more than two vinyl groups can be cited, and preferably a multifunctional (meth)acrylate having more than two (meth)acryloyl groups can be cited. If a multifunctional monomer is used, it is easy to adjust the adhesive force of the adhesive layer to within an appropriate range.

[0121] As multifunctional (meth) acrylate, there is no particular limitation, and in addition to hexanediol di(meth) acrylate, ethoxylated bisphenol A di(meth) acrylate, tri(2-hydroxyethyl) isocyanurate triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated glyceryl triacrylate, neopentyl glycol adipate diacrylate, etc., there are also polymers such as polyethylene glycol di(meth) acrylate, polypropylene glycol di(meth) acrylate, and liquid hydrogenated 1,2-polybutadiene di(meth) acrylate. Among these multifunctional (meth) acrylates, polymers are preferred, and liquid hydrogenated 1,2-polybutadiene diacrylate is more preferred. As commercially available products of liquid hydrogenated 1,2-polybutadiene diacrylate, "TEAI-1000" manufactured by Nippon Soda Co., Ltd. can be cited.

[0122] In addition, in the adhesive layer, the content of the structural unit derived from the crosslinking agent is preferably 0.1 to 4 parts by mass, more preferably 0.3 to 3 parts by mass, and further preferably 0.5 to 2 parts by mass, relative to 100 parts by mass of the structural unit derived from the (meth) alkyl ester monomer (A). If the content of the crosslinking agent is within the above range, it is easy to adjust the storage modulus and adhesive force of the adhesive layer to an appropriate range.

[0123] (Tackifying resin)

[0124] From the viewpoint of improving bonding strength, acrylic adhesive can contain tackifier resin. As tackifier resin, preferably tackifier resin with low polymerization hindrance such as hydrogenated terpene resin, hydrogenated rosin, disproportionated rosin resin, petroleum resin. Among them, if tackifier resin has more double bonds, polymerization reaction will be hindered, therefore, preferably tackifier resin of hydrogenated system, wherein, preferably hydrogenated petroleum resin.

[0125] From the viewpoint of improving the cohesive force and adhesive force of the adhesive, the softening point of the tackifier resin may be about 95° C. or higher, but preferably contains a tackifier resin with a softening point of 120° C. or higher. For example, a tackifier resin with a softening point of 95° C. or higher and lower than 120° C. and a tackifier resin with a softening point of 120° C. or higher and 150° C. or lower may be used in combination. It should be noted that the softening point can be measured by the ring and ball method specified in JIS K2207.

[0126] The content of the tackifier resin in the acrylic pressure-sensitive adhesive is preferably 5 to 40 parts by mass, more preferably 7 to 35 parts by mass, and even more preferably 10 to 25 parts by mass, based on 100 parts by mass of the structural unit derived from the (meth)acrylic acid alkyl ester monomer (A).

[0127] (particle)

[0128] The acrylic adhesive may contain fine particles. The inclusion of fine particles can enhance the adhesive strength.

[0129] Examples of the microparticles include inorganic hollow particles such as glass balls, volcanic ash hollow balls and fly ash balloons; organic hollow particles made of polymethyl methacrylate, acrylonitrile-vinylidene chloride copolymer, polystyrene and phenolic resin; inorganic microparticles such as glass beads, silica beads and synthetic mica; and organic microparticles such as polyethyl acrylate, polyurethane, polyethylene and polypropylene.

[0130] The content of the fine particles in the acrylic pressure-sensitive adhesive is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.7 to 5 parts by mass, based on 100 parts by mass of the structural unit derived from the (meth)acrylic acid alkyl ester monomer (A).

[0131] (Other ingredients)

[0132] The acrylic adhesive used in the adhesive layer may contain various additives conventionally used for adhesives, such as a plasticizer, a softener, a pigment, a dye, a dispersant, a photopolymerization initiator, and a flame retardant, in addition to the above-mentioned components.

[0133] (Acrylic Adhesive and Method for Producing Adhesive Layer)

[0134] The acrylic adhesive can be obtained by irradiating light to an adhesive composition comprising the above-mentioned polymerizable monomer and a sacrificial anticorrosion metal and a conductive material as needed to polymerize the polymerizable monomer. In addition, the adhesive composition can contain at least one of the above-mentioned tackifying resin, microparticles and other components as needed.

[0135] To explain more specifically, first, a polymerizable monomer, a sacrificial anticorrosion metal and a conductive material as required, a tackifier resin as required, fine particles and other components are placed in a reaction vessel such as a glass container and mixed to obtain an adhesive composition.

[0136] Next, in order to remove dissolved oxygen in the adhesive composition, an inert gas such as nitrogen is usually supplied to purge oxygen. Then, the adhesive composition is applied to a release sheet or a support such as a resin film, a fabric, or a nonwoven fabric, and then irradiated with light to polymerize the polymerizable monomer, thereby obtaining an adhesive layer.

[0137] The steps from coating or impregnation of the adhesive composition to irradiation with light are preferably performed in an inert gas atmosphere or in a state where oxygen is blocked by a film or the like.

[0138] In the present production method, the pressure-sensitive adhesive composition obtained by mixing the components may be prepolymerized to increase the viscosity before being applied to a release sheet, a support, or the like.

[0139] (Rubber-based adhesive)

[0140] Next, the rubber adhesive for the adhesive layer is described. The rubber adhesive contains a rubber component and a tackifying resin. As the rubber component, a styrene-isoprene block copolymer is preferably used. The diblock rate of the styrene-isoprene block copolymer is preferably 25 to 70% by mass, more preferably 30 to 65% by mass, and further preferably 45 to 60% by weight. The so-called diblock here refers to a diblock composed of styrene and isoprene. By making the diblock rate within the above range, it is easy to improve the adhesive force. It should be noted that in the styrene-isoprene block copolymer, in addition to the diblock, it also contains a triblock composed of styrene, isoprene, and styrene blocks, etc., which have more than 3 blocks.

[0141] The amount of styrene in the styrene-isoprene block copolymer is not particularly limited, but is preferably 14 to 24% by mass, more preferably 15 to 18% by mass. If the amount of styrene is 14% by mass or more, it is easy to become an adhesive with high cohesiveness. In addition, if it is set to 24% by mass or less, the cohesive force is of appropriate size and it is easy to show adhesive strength.

[0142] The molecular weight of the styrene-isoprene block copolymer is not particularly limited, but is preferably 100,000 to 400,000, more preferably 150,000 to 250,000 in terms of mass average molecular weight. The mass average molecular weight here refers to a molecular weight measured as a molecular weight in terms of polystyrene by GPC (gel permeation chromatography).

[0143] Various tackifier resins can be used for the tackifier resin of rubber-based adhesives, but petroleum resins, terpene resins, and coumarone resins are preferably used. One tackifier resin can be used alone, or two or more can be used in combination, but a petroleum resin and at least one resin selected from terpene resins and coumarone resins are preferably used in combination. By combining such tackifier resins, it is easy to make the adhesive force good.

[0144] Examples of the petroleum resin include aliphatic petroleum resin (C5 petroleum resin), alicyclic petroleum resin, aromatic petroleum resin, etc. From the viewpoint of compatibility with the styrene-isoprene block copolymer, aliphatic petroleum resin is preferred. In addition, the petroleum resin preferably has a softening point of about 90 to 120°C.

[0145] As the terpene resin, a terpene resin having a softening point of about 80 to 120° C. can be used, and from the viewpoint of ensuring adhesive strength, a terpene resin having a softening point of less than 100° C. is preferred. As the coumarone resin, a coumarone resin having a softening point of preferably 110 to 130° C., more preferably 115 to 125° C. is used in order to ensure cohesive strength.

[0146] The tackifier resin is preferably 60 to 250 parts by mass, more preferably 100 to 200 parts by mass, and further preferably 110 to 180 parts by mass relative to 100 parts by mass of the rubber component. By making the amount of the tackifier resin blended within the above range, the cohesive force can be improved and appropriate adhesive force can be imparted.

[0147] In addition, when a petroleum resin and at least one resin selected from a terpene resin and a coumarone resin are used in combination, the petroleum resin is preferably 50 to 200 parts by mass, preferably 60 to 150 parts by mass, and more preferably 60 to 110 parts by mass relative to 100 parts by mass of the rubber component. On the other hand, the terpene resin is preferably 10 to 70 parts by mass, more preferably 20 to 60 parts by mass, and further preferably 30 to 50 parts by mass relative to 100 parts by mass of the rubber component. In addition, the coumarone resin is preferably 10 to 60 parts by mass, more preferably 15 to 50 parts by mass, and further preferably 20 to 40 parts by mass relative to 100 parts by mass of the rubber component.

[0148] The rubber-based adhesive may contain the above-mentioned fine particles similarly to the acrylic-based adhesive. In addition, the rubber-based adhesive may contain a sacrificial anticorrosion metal, a conductive material, a softener, an antioxidant, a filler, and the like as necessary.

[0149] (Urethane adhesive)

[0150] The above-mentioned urethane adhesive is not particularly limited, and for example, urethane resins obtained by reacting at least a polyol with a polyisocyanate compound can be cited. As the above-mentioned polyol, for example, polyether polyol, polyester polyol, polycarbonate polyol, polycaprolactone polyol, etc. can be cited. As the above-mentioned polyisocyanate compound, for example, diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, etc. can be cited. These urethane adhesives can be used alone, or two or more can be used in combination.

[0151] In addition, as the urethane adhesive, a urethane resin obtained by reacting a polyurethane polyol with a multifunctional isocyanate curing agent can also be used. The polyurethane polyol can include a polyurethane polyol obtained by reacting the above-mentioned polyol with a polyisocyanate compound, or a polyurethane polyol obtained by reacting a polyol and a polyisocyanate compound with a chain extender such as a diamine. As the multifunctional isocyanate curing agent, any compound having two or more isocyanate groups can be used, and the above-mentioned isocyanate compound can be used.

[0152] The urethane adhesive may contain the above-mentioned fine particles in addition to the urethane resin. Furthermore, the urethane adhesive may contain a tackifier resin, a sacrificial anticorrosion metal, a conductive material, a softener, an antioxidant, a filler, etc. as necessary.

[0153] (Silicone adhesive)

[0154] In addition, examples of silicone adhesives include addition reaction type, peroxide curing type, or condensation reaction type silicone adhesives. Among them, addition reaction type silicone adhesives are preferably used from the viewpoint of being able to cure at low temperature in a short time. It should be noted that addition reaction type silicone adhesives are adhesives that cure when forming an adhesive layer. When an addition reaction type silicone adhesive is used as the silicone adhesive, the silicone adhesive may contain a catalyst such as a platinum catalyst.

[0155] The silicone-based adhesive may contain fine particles, and may also contain a cross-linking agent or various additives for controlling adhesive strength.

[0156] (Storage modulus)

[0157] The storage modulus of the adhesive layer at 23°C is preferably 50,000 to 1,000,000 Pa. If the storage modulus at 23°C is within the above range, when the adhesive layer is damaged by external impact, etc., the ability to restore the damaged part (hereinafter also referred to as self-repairing ability) becomes stronger. As a result, the generation of rust can be suppressed and the anti-corrosion performance is improved.

[0158] From the viewpoint of increasing the self-repairing ability and improving the anti-corrosion performance, the storage modulus of the adhesive layer at 23° C. is more preferably 200,000 to 800,000 Pa, and even more preferably 300,000 to 700,000 Pa.

[0159] The storage modulus can be calculated by measuring a dynamic viscoelastic spectrum using, for example, DVA-200 (manufactured by ITECH Instruments Co., Ltd.) under the conditions of shear mode: 10 Hz, strain: 0.1%, temperature range: -100°C to 100°C, and heating rate: 10°C / min.

[0160] (thickness)

[0161] The thickness of the adhesive layer is preferably 50 to 3000 μm, more preferably 100 to 2000 μm, further preferably 120 to 1500 μm, further preferably 200 to 1200 μm, and particularly preferably 300 to 1000 μm. By making the thickness 50 μm or more, the self-repairing ability is increased, the corrosion resistance of the anti-corrosion adhesive tape can be improved, and the adhesive force is also easily increased. In addition, by making the thickness of the adhesive layer 3000 μm or less, the corrosion resistance performance improvement effect corresponding to the thickness can be obtained.

[0162] <Surface protection film>

[0163] When the adhesive layer is provided on one side of the substrate, the anti-corrosion adhesive tape of the present invention may further have a surface protection film provided on the surface of the substrate opposite to the surface of the adhesive layer and used to protect the surface of the substrate opposite to the surface of the adhesive layer.

[0164] The surface protective film in the anticorrosion adhesive tape of the present invention is not particularly limited as long as it is a resin film that can suppress deformation of the substrate (which is the cause of the wrinkles of the anticorrosion adhesive tape). As the resin film used for the surface protective film in the anticorrosion adhesive tape of the present invention, for example, polyester resin films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polypropylene resin films such as biaxially stretched polypropylene (OPP), polyamide resin films such as biaxially stretched nylon (ONy), polyimide resin films, polyacetal resin films, polycarbonate resin films, modified polyphenylene ether resin films, polyphenylene sulfide resin films, polysulfone resin films, polyether ketone resin films, biaxially stretched polypropylene, etc. can be cited. These resin films can be used alone or in combination of two or more. Among these resin films, at least one resin film selected from polyester resin films, polypropylene resin films and polyamide resin films is preferred from the viewpoint of suppressing the occurrence of wrinkles in the anticorrosion adhesive tape during large-area construction.

[0165] The thickness of the surface protection film is preferably 25 μm or more and 200 μm or less, more preferably 25 μm or more and 150 μm or less, further preferably 38 μm or more and 100 μm or less, and further preferably 38 μm or more and 75 μm or less. By making the surface protection film 25 μm or more, the generation of wrinkles of the anticorrosive adhesive tape during large-area construction can be further suppressed. In addition, by setting it to 200 μm or less, it is easy to improve the adhesion to the adherend.

[0166] The surface protection film can be directly laminated on the substrate, and from the viewpoint of ensuring a certain adhesive force for the substrate, it is preferably laminated via an adhesive layer. As an adhesive layer, it can be composed of a known adhesive, a bonding agent, or it can be composed of a thermoplastic resin. In the case of a thermoplastic resin, it is an adhesive layer also referred to as an approximate adhesive layer, and the surface protection film can be attached to the substrate via an approximate adhesive layer by thermal lamination, etc.

[0167] The method of laminating the substrate and the surface protection film may be performed by a known lamination method such as heat lamination, hot melt lamination, solventless lamination, wet lamination, dry lamination, extrusion coating lamination, or coextrusion lamination.

[0168] (Difference in tensile load)

[0169] In the anticorrosion adhesive tape of the present invention having a surface protective film, the difference between the tensile load when the laminate composed of the substrate and the surface protective film is elongated by 2.5% and the tensile load when it is elongated by 0.5% is preferably 2.5 N / mm or more and 6.0 N / mm or less. If the difference between the tensile load when the laminate composed of the substrate and the surface protective film is elongated by 2.5% and the tensile load when it is elongated by 0.5% is 2.5 N / mm or more, by attaching the anticorrosion adhesive tape to the adherend, it is possible to further suppress the generation of wrinkles in the anticorrosion adhesive tape during large-area construction. If the difference between the tensile load when the laminate composed of the substrate and the surface protective film is elongated by 2.5% and the tensile load when it is elongated by 0.5% is 6.0 N / mm or less, the anticorrosion adhesive tape can be more easily attached to the adherend. From this point of view, the difference between the tensile load at 2.5% elongation and the tensile load at 0.5% elongation of the laminate composed of the substrate and the surface protection film is more preferably 3.0 N / mm or more and 5.8 N / mm or less, and further preferably 3.2 N / mm or more and 5.5 N / mm or less. The difference between the tensile load at 2.5% elongation and the tensile load at 0.5% elongation of the laminate composed of the substrate and the surface protection film can be adjusted by the material and thickness of the surface protection film, the material and thickness of the substrate.

[0170] (Peel force)

[0171] The peeling force when peeling off the surface protection film from the anticorrosion adhesive tape of the present invention is, for example, 0.05N / m or more and 1.0N / m or less, preferably 0.1N / m or more and 0.6N / m or less. If the peeling force when peeling off the surface protection film from the substrate is 0.1N / m or more, the undesirable peeling of the surface protection film can be further suppressed. If the peeling force when peeling off the surface protection film from the anticorrosion adhesive tape is 0.6N / m or less, the surface protection film can be quickly peeled off from the anticorrosion adhesive tape, and the workability is further improved. From such a viewpoint, the peeling force when peeling off the surface protection film from the substrate is more preferably 0.1N / m or more and 0.4N / m or less, and more preferably 0.1N / m or more and 0.3N / m or less. It should be noted that the peeling force when peeling off the surface protection film from the substrate can be measured by the method described in the embodiments described later.

[0172] The peeling force when peeling the surface protection film from the substrate can be appropriately adjusted by the conditions of the lamination method, the material of the adhesive layer between the substrate and the surface protection film, and the like as described above.

[0173] <Presence of Rust in Cyclic Corrosion Test>

[0174] The anticorrosion adhesive tape of the present invention preferably does not generate rust in a cyclic corrosion test based on JIS K5600-7-9 (General Test Methods for Coatings - Part 7: Long-term Durability of Coatings - Section 9: Cyclic Corrosion Test Method - Salt Spray / Drying / Wetting, Cycle D). Since no rust is generated in the cyclic corrosion test, the anticorrosion adhesive tape of the present invention has excellent corrosion resistance. The generation of rust can be suppressed by adjusting the composition, thickness, etc. of the adhesive layer of the anticorrosion adhesive tape.

[0175] The presence or absence of rust generation in the cyclic corrosion test can be confirmed as follows.

[0176] The anticorrosion adhesive tape of the present invention is attached to the test plate specified in JIS K5600-7-9 to prepare a test piece. At this time, the test plate surface is attached in a manner that the adhesive layer of the anticorrosion adhesive tape is in contact with each other to prepare the test piece. The size of the anticorrosion adhesive tape is set to a length of 150 mm and a width of 70 mm.

[0177] Next, the test piece is given an incision scar from the side of the anticorrosion adhesive tape. The incision scar is formed by giving two linear scars in a cross manner (i.e., the scar is given in a manner that forms an x ​​symbol). At this time, the length of one scar is 70 mm, and the two scars intersect at an angle of 90°. In addition, the incision scar is given in a manner that reaches the test plate as a base using a single-edged incision tool as specified in JIS K5600-7-9.

[0178] Then, the test piece with the incision scar was subjected to a salt spray test in accordance with cycle D of Appendix 1 of JIS K5600-7-9. The test was performed for 28 cycles (a total of 168 hours).

[0179] The test piece after the salt spray test was observed to check the presence or absence of rust in the portion with the cut-in flaw.

[0180] In addition, when the anticorrosion adhesive tape of the present invention has a surface protection film, the above test is performed after peeling off the surface protection film.

[0181] <Adhesion after cyclic corrosion test>

[0182] The adhesive force of the anticorrosion adhesive tape of the present invention after the cyclic corrosion test based on JIS K5600-7-9 (General Test Methods for Coatings - Part 7: Long-term Durability of Coatings - Section 9: Cyclic Corrosion Test Method - Salt Spray / Drying / Wetting, Cycle D) is, for example, 10 N / 25 mm or more, preferably 20 N / 25 mm or more, more preferably 25 N / 25 mm or more, and further preferably 30 N / 25 mm or more. If the adhesive force is 20 N / 25 mm or more, long-term adhesive force can be sufficiently ensured, and the anticorrosion adhesive tape is not easily peeled off from the adherend such as steel, so that the reduction of corrosion resistance can be prevented.

[0183] On the other hand, the upper limit of the adhesive force is not particularly limited, but is preferably 200 N / 25 mm or less from a practical point of view.

[0184] The adhesive strength of the anticorrosion adhesive tape after the cyclic corrosion test can be measured as follows.

[0185] The anticorrosion adhesive tape of the present invention is attached to a stainless steel plate (SUS plate) to prepare a sample for evaluating adhesion. At this time, the SUS plate surface is attached in a manner that the adhesive layer of the anticorrosion adhesive tape is in contact with each other to prepare a sample for evaluating adhesion. The size of the anticorrosion adhesive tape 10 is set to a length of 100 mm and a width of 25 mm.

[0186] The sample for evaluating adhesive strength was used to perform a salt spray test in accordance with cycle D of Appendix 1 of JIS K5600-7-9. The test was performed for 28 cycles (a total of 168 hours).

[0187] For the samples for evaluating the adhesion after the salt spray test, a peel test of the anticorrosion adhesive tape was performed to measure the adhesion. The peel test was performed using a tensile tester at a peel angle of 180° and a speed of 300 mm / min, and the interval average of the detected load (N) was taken as the adhesion.

[0188] <Composition of Anti-corrosion Adhesive Tape>

[0189] The anti-corrosion adhesive tape of the present invention is as follows Figure 1 As shown, the anticorrosion adhesive tape 10 is preferably a single-sided adhesive tape having a substrate 12 and an adhesive layer 11 provided on one side of the substrate 12. Thus, the adhesive layer 11 can be protected by the substrate 12.

[0190] The anticorrosion adhesive tapes in the drawings are used in a manner such that the surface 11A of the adhesive layer 11 is attached to an adherend as an adhesive surface.

[0191] Although not shown in the drawings, the anticorrosion adhesive tape may be a double-sided adhesive tape having a substrate and adhesive layers provided on both surfaces of the substrate.

[0192] As described above, the adhesive layer in the present invention may not contain a metal having a lower potential than iron. In this case, in order to improve the corrosion resistance of the anticorrosive adhesive tape 10, Figure 2 As shown in the figure, the anti-corrosion adhesive tape 10 preferably further includes a metal layer 13 between the substrate 12 and the adhesive layer 11, and the metal layer 13 is a metal layer with a lower potential than iron. As the metal with a lower potential than iron, the above-mentioned metals can be used without particular limitation, but the metal layer 13 is more preferably a zinc layer. Specifically, the metal layer 13 can be bonded to the substrate 12 using an adhesive or the like, or can be formed on the substrate 12 by sputtering, vacuum evaporation, etc. In addition, the metal layer 13 can also be a metal film obtained by forming a film on the surface of the adhesive layer 11 by sputtering, vacuum evaporation, etc.

[0193] The metal layer 13 is directly formed on the adhesive layer 11 in a form of being sandwiched between the base material 12 and the adhesive layer 11. That is, the metal having a lower potential than iron constituting the metal layer 13 is in contact with the adhesive layer 11. When the metal having a lower potential than iron is in contact with the adhesive layer 11 in this way, the electrons released during ionization can easily migrate to the adhesive layer 11, thereby improving the corrosion resistance of the anti-corrosion adhesive tape 10. In addition, in this case, from the viewpoint of the corrosion resistance of the anti-corrosion adhesive tape 10, the adhesive layer 11 also preferably contains a conductive material other than the metal having a lower potential than iron.

[0194] The thickness of the metal layer 13 is preferably 2.5 μm or more. If the thickness of the metal layer 13 is 2.5 μm or more, the metal layer 13 can fully supply electrons by ionization of the metal in the metal layer 13, and can maintain the sufficient corrosion resistance of the anti-corrosion adhesive tape 10. From the viewpoint of improving the corrosion resistance of the anti-corrosion adhesive tape 10, the thickness of the metal layer 13 is more preferably 5 μm or more. In addition, from the viewpoint of ensuring the flexibility of the anti-corrosion adhesive tape 10 and making the operability of the anti-corrosion adhesive tape 10 good, and from the viewpoint of making it easy to make the anti-corrosion adhesive tape close to the adherend having a complex shape, the thickness of the metal layer 13 is preferably 200 μm or less, and more preferably 100 μm or less.

[0195] The anti-corrosion adhesive tape of the present invention may have a release sheet attached to the surface of the adhesive layer. The release sheet may be peeled off from the adhesive layer before using the anti-corrosion adhesive tape to expose the adhesive layer, and the exposed adhesive layer may be attached to an adherend. More specifically, the release sheet may be attached to the surface of the adhesive layer opposite to the surface on which the substrate 12 or the metal layer 13 is provided, that is, the surface 11A.

[0196] As the release sheet, a resin film may be used, but the surface to be bonded to the pressure-sensitive adhesive layer is preferably a release-treated surface that has been subjected to a release treatment using a silicone release agent or the like.

[0197] [Applications of anti-corrosion adhesive tape]

[0198] The anti-corrosion adhesive tape of the present invention is used for attaching to various adherends to protect the adherends from corrosion. The anti-corrosion adhesive tape of the present invention has excellent adhesion and corrosion resistance, so it is preferably attached to the surface of an adherend made of various metal materials or the surface of an adherend made of concrete for use. As the metal material, it is preferably a metal material containing at least one metal selected from iron and an alloy containing iron. As the alloy containing iron, specifically, various steel materials such as alloy steels such as nickel-chromium steel, nickel-chromium-molybdenum steel, chrome steel, chrome-molybdenum steel, and manganese steel, and carbon steel can be cited.

[0199] The anticorrosion adhesive tape of the present invention is preferably used for adherends with complex surface shapes. As specific adherends, adherends with concavoconvex surfaces can be cited, and for example, components with a welding portion formed by joining two components by welding can be cited. In the component with a welding portion, the welding portion is a convex portion. As an adherend with a welding portion, welded piping can be cited. In the welded piping, the joint portion connecting two pipings is a welding portion. For an adherend with a welding portion, the anticorrosion adhesive tape can be attached in a manner that covers the welding portion.

[0200] Even if the weld is usually coated with an anti-rust paint, it will drip until it is cured, so that the film thickness after curing becomes thinner than the required film thickness, and sometimes cracks are generated and the crack surface is exposed, which makes it easier to rust. However, by attaching the anti-corrosion adhesive tape of the present invention, rust in such welds can be properly prevented. In addition, the anti-corrosion adhesive tape of the present invention will not crack even if it is attached to an adherend with a complex surface shape such as a weld, and can ensure high adhesion and tracking properties, so that it can exert excellent corrosion resistance.

[0201] In addition, the anti-corrosion adhesive tape of the present invention can suppress the generation of wrinkles, floating and cracks during large-area construction, and therefore can be suitably used for large-area construction. Specifically, the anti-corrosion adhesive tape can be, for example, 200 cm 2 Above, 300cm 2 Above, 400cm 2 Above, 500cm 2 Above, preferably 2000cm 2 More preferably 3000cm 2 More preferably, 4000 cm 2 More preferably, 5000 cm 2 The size of the anticorrosion adhesive tape is not particularly limited, but is, for example, 100,000 cm 2 , preferably 50000cm 2 , more preferably 25000cm 2 , and more preferably 10000cm 2 .

[0202] After being attached to an adherend, the anticorrosion adhesive tape of the present invention can be attached to various adherends by being pressed while being heated to, for example, 90 to 150° C., preferably 90 to 130° C. By attaching the adhesive tape to the adherend while being heated, the adhesive tape can be attached to the adherend with higher adhesion and tracking properties, and high corrosion resistance can be easily ensured. It should be noted that the adhesive tape can be heated by a known heating device such as an industrial dryer.

[0203] The anti-corrosion adhesive tape of the present invention can be used for repair purposes, which refers to anti-corrosion treatment of metal materials such as steel and concrete constituting existing structures such as bridges, iron towers, viaducts, tanks, factory equipment, bridge piers, and pipes.

[0204] [Structure]

[0205] The structure of the present invention comprises the anticorrosion adhesive tape of the present invention and an adherend made of a metal material or an adherend made of concrete, and the anticorrosion adhesive tape of the present invention is attached to the surface of the adherend.

[0206] As described above, the anti-corrosion adhesive tape of the present invention can suppress the generation of wrinkles, floating and cracks during large-area construction, and therefore can be suitably used for large-area construction. From this point of view, the attachment area of ​​the anti-corrosion adhesive tape of the present invention in the structure of the present invention is, for example, 200 cm 2 Above, 300cm 2 Above, 400cm 2 Above, 500cm 2 Above, preferably 2000cm 2 More preferably 3000cm 2 More preferably, 4000 cm 2 More preferably, 5000 cm 2 The upper limit of the range of the adhesion area of ​​the anticorrosion adhesive tape of the present invention in the structure of the present invention is not particularly limited, and is, for example, 100,000 cm 2 , preferably 50000cm 2 , more preferably 25000cm 2 , more preferably 10000cm 2 .

[0207] [Anti-corrosion method]

[0208] The anticorrosion method of the present invention comprises the following steps: the first step: preparing the anticorrosion adhesive tape of the present invention having a surface protection film, and the second step: attaching the anticorrosion adhesive tape to an adherend and then peeling off the surface protection film from the anticorrosion adhesive tape. Thus, when constructing over a large area, the generation of wrinkles on the anticorrosion adhesive tape can be suppressed. The steps of the anticorrosion method of the present invention are described below.

[0209] (1st step)

[0210] In the first step, the anticorrosion adhesive tape of the present invention having a surface protection film is prepared. The anticorrosion adhesive tape of the present invention has been described in the section of anticorrosion adhesive tape, so the description of the anticorrosion adhesive tape of the present invention is omitted.

[0211] (Second step)

[0212] In the second step, the anticorrosion adhesive tape is attached to an adherend and then the surface protection film is peeled off from the anticorrosion adhesive tape.

[0213] The shape of the adherend is not particularly limited, and may be a flat surface or a shape having corners such as H-steel. In addition, the adherend may be attached to a portion having a curved surface.

[0214] The adherend to which the anticorrosion method of the present invention is applied is not particularly limited, and examples thereof include buildings, air conditioning equipment, construction equipment, buried pipes, sanitary equipment, chemical plant equipment, lifelines such as roads and bridges, automobiles, railway vehicles, ships, tanks, electrical equipment, electronic equipment, etc. In addition, as the material of the adherend, as described above, preferably metal materials such as steel and concrete, and more specifically, concrete structures and steel structures are particularly preferred.

[0215] Example

[0216] Hereinafter, the present invention will be described in more detail using Examples, but the present invention is not limited to these Examples.

[0217] [Measurement and evaluation methods]

[0218] In each of the Examples and Comparative Examples, the anticorrosion adhesive tape was measured and evaluated by the following methods.

[0219] <Difference in tensile load>

[0220] For the substrates used in each embodiment and comparative example, a tensile tester was used to measure the tensile load when stretched by 2.5% and the tensile load when stretched by 0.5%, and the difference between the two was calculated. It should be noted that the measurement was performed in each direction in the MD direction and the TD direction, and the difference between the tensile load when the anti-corrosion adhesive tape was stretched by 2.5% and the tensile load when the anti-corrosion adhesive tape was stretched by 0.5% was calculated for each direction. The larger median of the calculated difference in tensile load in the MD direction and the TD direction was taken as the difference in tensile load. It should be noted that the measurement conditions are shown below.

[0221] Sample size: width 24mm × length 80mm

[0222] Distance between chucks: 50mm

[0223] Stretching speed: 300mm / min

[0224] <Tear Strength>

[0225] The measurement was performed by the same method as the Elmendorf tear method according to JIS K7128-2 (1998), except that the notch was not cut in the sample. The measurement was performed in both MD and TD, and the smaller value was taken as the tear strength (N) of the substrate.

[0226] <Storage modulus at 23°C>

[0227] The storage modulus of the adhesive layer of the anti-corrosion adhesive tape at 23°C was calculated by measuring the dynamic viscoelastic spectrum using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., trade name "DVA-200") under the conditions of shear mode: 10 Hz, strain: 0.1%, temperature range: -100°C to 100°C, and heating rate: 10°C / min.

[0228] <Presence or absence of rust generation in the cyclic corrosion test>

[0229] By the method described in the specification, in JIS K5600-7-9 (General test methods for paints - Part 7: Long-term durability of paint films - Section 9: Cyclic corrosion test method - Salt spray / drying / humidification, cycle D), the presence or absence of rust generation in the cut scar portion was visually confirmed.

[0230] <Adhesive force>

[0231] 1. Preparation of specimens

[0232] On a SUS plate (width 50 mm, length 125 mm), the anti-corrosion adhesive tape (width 25 mm, length 100 mm) of each example and comparative example was attached by moving a 2-kg roller back and forth twice at a speed of 10 ± 0.5 mm / s to prepare a specimen for evaluating the adhesive force. Using this specimen for evaluating the adhesive force, the initial adhesive force (adhesive force before the test) was measured.

[0233] 2. Measurement of adhesive force

[0234] Using the specimen obtained in 1. above, the cyclic D corrosion resistance test based on JIS K5600-7-9 was carried out for 168 hours. Then, the specimen was fixed to the chuck of a tensile testing machine ("Tensilon universal material testing machine" manufactured by A&D Co., Ltd.). Further, then, in an environment of 23°C and 50% RH, the anti-corrosion adhesive tape was stretched by 60 mm or more at a peeling angle of 180° and a speed of 300 mm / min, and the interval average value of the load (N) detected by the load sensor was recorded and used as the adhesive force.

[0235] <Practical evaluation of convexity followability>

[0236] The evaluation of convexity followability was carried out through the steps shown in 1. to 4. below.

[0237] 1. As Figure 3 shown, on the adherend surface 20A of the L-shaped SUS plate 20, the anti-corrosion adhesive tape 10 (30 mm square) was attached so that the height h and width t measured from the corner were 2 mm.

[0238] 2. The portion of the anticorrosion adhesive tape 10 that is not bonded to the L-shaped SUS plate 20 is pressed against the scraper.

[0239] 3. After the pressing in 2. above, the height h was measured and the presence or absence of cracks in the anticorrosion adhesive tape 10 was visually confirmed. If cracks were generated in the anticorrosion adhesive tape 10 during the pressing, the height h was recorded as 2 mm.

[0240] 4. Based on the measured value of the height h obtained in 3. above, the convex portion followability of the anticorrosion adhesive tape 10 was evaluated according to the following criteria.

[0241] A··No lifting occurred (height h was 0 mm), and no crack occurred in the anticorrosion adhesive tape 10 .

[0242] B··Floating occurs (height h is greater than 0 mm), or cracks occur in the anticorrosion adhesive tape 10 .

[0243] C··Floating occurred (height h was greater than 0 mm), and cracks occurred in the anticorrosion adhesive tape 10 .

[0244] <Evaluation of large-area construction performance>

[0245] like Figure 4 As shown in the figure, the anticorrosion adhesive tape 10 (width 100 mm, length 520 mm) of each embodiment and comparative example was attached to the H-steel 30 in the order of the upper flange upper surface 31, the edge surface 32, the upper flange lower surface 33 and the waist plate 34 of the H-steel 30. Five evaluators were asked to perform the above-mentioned attachment operation within 30 seconds, and the large-area workability of the anticorrosion adhesive tape was evaluated according to the following evaluation criteria.

[0246] A·· Three or more of the five evaluators observed no wrinkles, lifting, or cracks in the anticorrosion adhesive tape affixed to H-steel.

[0247] B··Three or more of the five evaluators observed at least one defect among wrinkles, lifting, and cracks in the anticorrosion adhesive tape attached to H steel.

[0248] <Weather resistance (gloss retention)>

[0249] The anti-corrosion adhesive tape (width 25 mm, length 100 mm) of each embodiment and comparative example was attached, and the mirror glossiness of the surface of the tape, and thus the substrate side, was measured using a gloss meter (manufactured by Horiba, Ltd., product name: "IG-340"). In the measurement of the mirror glossiness, the gloss meter with a geometric condition of 60° was used in accordance with JIS K 5600-4-7. The mirror glossiness obtained by the measurement at this time is referred to as mirror glossiness A. Then, for the tape, an accelerated weathering test based on cycle A in JIS K5600-7-7 was carried out for 500 hours. After the accelerated weathering test was carried out, the mirror glossiness of the substrate of the tape was measured by the same method as that performed before the test. The mirror glossiness obtained by the measurement after the test is referred to as mirror glossiness B.

[0250] The gloss retention rate of the substrate of the tape was calculated using the two types of specular glossiness obtained as described above. The formula for calculating the gloss retention rate is as follows.

[0251] Gloss retention rate (%) = (specular gloss B / specular gloss A) × 100

[0252] A··Gloss retention rate is more than 90%

[0253] B. Gloss retention rate is 80% or more and less than 90%

[0254] C··Gloss retention rate is less than 80%

[0255] <Practical evaluation of peeling>

[0256] The anti-corrosion adhesive tape (width 25 mm, length 100 mm) of each embodiment and comparative example was attached to a SUS plate (width 50 mm, length 125 mm), and cured at 23°C for 3 days to prepare a sample for peeling evaluation. From the spraying position obliquely above the anti-corrosion adhesive tape in the peeling evaluation sample, water was sprayed toward the surface of the end side of the long side direction of the anti-corrosion adhesive tape under a water pressure of 8 MPa for 5 minutes. It should be noted that the position of spraying water (spraying position) is a position where the angle between the line connecting the spraying position and the central part of the end of the anti-corrosion adhesive tape and the SUS plate is 30°, and is a position directly above a point 5 cm away from the central part of the end of the anti-corrosion adhesive tape in the horizontal direction.

[0257] The distance of the anticorrosion adhesive tape peeling off after spraying water was measured and evaluated according to the following criteria.

[0258] A··The peeling distance is 0 mm or more and less than 15 mm

[0259] B··The peeling distance is more than 15mm and less than 25mm

[0260] C··Peeling distance is more than 25mm

[0261] [Materials used]

[0262] In each of the Examples and Comparative Examples, the following materials were used.

[0263] <Adhesive Layer>

[0264] ·2-Ethylhexyl acrylate

[0265] n-Butyl acrylate

[0266] ·acrylic acid

[0267] Olefin polymer: Product name "L-1253", manufactured by Kuraray Co., Ltd., hydrogenated polybutadiene having a (meth)acryloyl group at one end

[0268] Tackifier resin 1: product name "Alcon P140", manufactured by Arakawa Chemical Industries, Ltd., hydrogenated petroleum resin, softening point 140°C

[0269] Tackifier resin 2: product name "Alcon P100", manufactured by Arakawa Chemical Industries, Ltd., hydrogenated petroleum resin, softening point 100°C

[0270] · Microparticles: Product name: "Celstar Z-27", manufactured by Tokai Industry Co., Ltd., glass spheres

[0271] Zinc particles: manufactured by Sakai Chemical Industry Co., Ltd., product name "Zinc Dust #40", average particle size: 50 μm

[0272] Carbon nanotube (CNT): manufactured by JEIO Corporation, product name "JENOTUBE8A", average diameter 6-9nm, average length 100-200μm

[0273] Dispersant: manufactured by Sekisui Chemical Co., Ltd., trade name "Esleck BX-L", polyvinyl butyral resin

[0274] Cross-linking agent: Product name "TEAI-1000", manufactured by Nippon Soda Co., Ltd.

[0275] Polymerization initiator: 2,2-dimethoxy-2-phenylacetophenone

[0276] <Film>

[0277] PET: Polyethylene terephthalate film, product name "Lumira S10", manufactured by Toray Co., Ltd.

[0278] OPP: Oriented polypropylene film, product name "パイレン P2161", manufactured by Toyobo Co., Ltd.

[0279] ·Acrylic: acrylic resin film, product name "Acrylic Pren MBS121E", manufactured by Mitsubishi Chemical Co., Ltd.

[0280] LL / Ny / LL: Multilayer film having a structure of linear low-density polyethylene / nylon / linear low-density polyethylene: Product name: "Diamilon MF F124" manufactured by Mitsubishi Chemical Co., Ltd.

[0281] It should be noted that, for some of the resin films, a resin film having a coating film of a fluororesin on the surface was used. The coating film was formed on the surface of the substrate opposite to the surface on which the adhesive layer was provided. The presence or absence of the coating film was as shown in the table.

[0282] [Examples 1 to 8, Comparative Examples 1 to 3]

[0283] An adhesive composition was prepared according to the formulation described in Table 1. The adhesive composition was purged with nitrogen to remove dissolved oxygen. Next, the adhesive composition was applied to the film. Then, the film was irradiated with ultraviolet light at an intensity of 5 mW / cm 2 The intensity of the chemical lamp was adjusted in a manner of , and ultraviolet rays were irradiated for 15 minutes to obtain an anti-corrosion adhesive tape. It should be noted that the components of the adhesive composition and the film coated with the adhesive composition are as described above.

[0284] [Table 1]

[0285]

[0286] As can be seen from the above examples, the anticorrosion adhesive tapes prepared in Examples 1 to 8 that meet the requirements of the present invention have excellent adhesion to adherends having complex surface shapes and can suppress the occurrence of wrinkles, lifting and cracks during large-area construction.

[0287] In contrast, in the anticorrosion adhesive tape prepared in Comparative Example 1, the tear strength of the substrate was less than 1.7 N, so the adhesion to the adherend with a complex surface shape was poor, and floating and cracks occurred during large-area construction. In addition, since the substrate did not have a coating film, the gloss retention rate was slightly reduced.

[0288] In addition, in the anticorrosion adhesive tape prepared in Comparative Example 2, the difference in tensile load of the base material was less than 1.5 N / mm, and therefore wrinkles were generated during application over a large area.

[0289] In the anticorrosion adhesive tape prepared in Comparative Example 3, the difference in tensile load of the base material was larger than 6.0 N / mm, and thus, lifting occurred during construction over a large area.

[0290] Description of Reference Numerals

[0291] 10. Adhesive tape for corrosion protection

[0292] 11 Adhesive layer

[0293] 12 Base material

[0294] 13 Metal Layer

[0295] 20L type SUS plate

[0296] 20A Adhesive surface

[0297] 30H Steel

[0298] hHeight

[0299] Width

Claims

1. An anti-corrosion adhesive tape comprising a substrate and an adhesive layer provided on at least one side of the substrate, The difference between the tensile load of the substrate when it is elongated by 2.5% and the tensile load when it is elongated by 0.5% is 1.5 N / mm or more and 6.0 N / mm or less, The tear strength of the substrate measured by the Elmendorf tear method in accordance with JIS K7128-2 (1998) without cutting is 1.7 N or more. 2 . The anticorrosion adhesive tape according to claim 1 , wherein no rust is generated in a cyclic corrosion test based on cycle D in JIS K5600-7-9, and the adhesive strength after the cyclic corrosion test is 20 N / 25 mm or more. 3 . The anticorrosion adhesive tape according to claim 1 , wherein the gloss retention of the substrate is 80% or more after an accelerated weathering test based on Cycle A in JIS K5600-7-7 is performed for 500 hours. 4 . The anticorrosion adhesive tape according to claim 1 , wherein the base material has a thickness of 20 to 150 μm. 5 . The anticorrosion adhesive tape according to claim 1 , wherein the substrate is a resin film having a coating film on the surface thereof. 6 . The anticorrosion adhesive tape according to claim 5 , wherein the resin film is at least one resin film selected from the group consisting of a polyethylene terephthalate (PET) film, an oriented polypropylene (OPP) film, an acrylic resin film, and a polyamide resin film. 7 . The anticorrosion adhesive tape according to claim 1 , wherein the adhesive layer contains a metal having a lower electric potential than iron.

8. The anticorrosion adhesive tape according to claim 7, wherein the metal having a lower electric potential than iron is zinc. 9 . The anticorrosion adhesive tape according to claim 7 , wherein the adhesive layer contains a conductive material other than the metal having a lower potential than iron. 10 . The anticorrosion adhesive tape according to claim 9 , wherein the conductive material is carbon nanotubes. 11 . The anticorrosion adhesive tape according to claim 1 , wherein the adhesive layer is formed of an acrylic adhesive. 12 . The anticorrosion adhesive tape according to claim 1 , further comprising a metal layer between the substrate and the adhesive layer, wherein the metal layer has a lower potential than iron. 13 . The anticorrosion adhesive tape according to claim 12 , wherein the metal layer is a zinc layer. 14 . The anticorrosion adhesive tape according to claim 1 , wherein the adhesive layer has a thickness of 50 to 3000 μm. 15 . The anticorrosion adhesive tape according to claim 1 , wherein the adhesive layer has a storage modulus of 50,000 to 1,000,000 Pa at 23° C.

16. The anticorrosion adhesive tape according to claim 1 to 15, wherein the adhesive layer is provided on one side of the substrate. The anticorrosion adhesive tape further includes a surface protection film provided on the surface of the substrate opposite to the adhesive layer side surface and used to protect the surface of the substrate opposite to the adhesive layer side surface.

17. A structure comprising the anti-corrosion adhesive tape according to any one of claims 1 to 16 and an adherend made of a metal material or an adherend made of concrete, wherein the anti-food adhesive tape is attached to a surface of the adherend.

18. The structure according to claim 17, wherein the anti-corrosion adhesive tape has an attachment area of ​​2000 cm 2 above.

19. A corrosion prevention method comprising the following steps: Step 1: preparing the anticorrosion adhesive tape according to claim 16, and Second step: after attaching the anticorrosion adhesive tape to an adherend, peeling the surface protection film from the anticorrosion adhesive tape.

Citation Information

Patent Citations

  • ANTICORROSIve MEMBER AND ANTICORROSION METHOD

    JP2019127606A